Fluorosilane interface modified foam metal-polytetrafluoroethylene interpenetrating phase composite material and preparation method thereof

By modifying the foam metal frame with fluorosilane modification, combining the structural parameter regulation of foam metal and optimization of composite material preparation process, the problems of insufficient thermal conductivity, mechanical strength and wear resistance of traditional polytetrafluoroethylene lubricating materials are solved, and a high-performance foam metal-polytetrafluoroethylene interpenetrating composite material is achieved.

CN119529450AActive Publication Date: 2025-02-28LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411635245.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-28
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Traditional composite modified polytetrafluoroethylene lubricating materials fail lubrication during friction due to insufficient thermal conductivity, mechanical strength and wear resistance. The thermal expansion coefficients of metal and polymer during high-temperature sintering lead to interface separation, reducing material performance.

Method used

The foam metal skeleton is modified and modified by fluorosilane coupling agent to enhance the bonding degree of the three-dimensional continuous interface of foam metal-polytetrafluoroethylene, and to regulate the structural parameters of foam metal and the preparation process of composite materials, the thermal conductivity, mechanical strength and wear resistance of the material are improved.

Benefits of technology

It significantly improves the thermal conductivity, mechanical strength and wear resistance of the foam metal-Polytetrafluoroethylene interpenetrating composite material, improves the interface combination of the material during high-temperature sintering, and extends the service life of the lubricating material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529450A_ABST
    Figure CN119529450A_ABST
Patent Text Reader

Abstract

The invention provides a fluorosilane interface modified foam metal-polytetrafluoroethylene interpenetrating phase composite material and a preparation method thereof.The fluorosilane interface modified foam metal-polytetrafluoroethylene interpenetrating phase composite material is prepared by taking polytetrafluoroethylene emulsion as a main base material, taking three-dimensional continuous open-cell foam metal as a reinforcing framework, taking a fluorosilane-containing coupling agent as an interface modification material and taking polytetrafluoroethylene as a filler. The material is prepared and formed through fluorosilane interface modification, polytetrafluoroethylene emulsion impregnation and high-temperature free sintering. The foam metal is subjected to fluorosilane coupling agent interface modification through reaction condition regulation and control and fluorosilane type selection, and interface bonding of the foam metal and a polytetrafluoroethylene matrix is improved. In addition, the thermal conductivity, the mechanical strength and the wear resistance of the foam metal-polytetrafluoroethylene interpenetrating phase composite material are further improved by combining structural parameters of the foam metal and regulation and control of a composite material preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubricating materials, and in particular to a fluorosilane-modified interface-modified foam metal-polytetrafluoroethylene interpenetrating phase composite material and a preparation method thereof. Background Art

[0002] Interpenetrating composite materials are materials formed by two or more constituent phases interconnected in a three-dimensional structure. Interpenetrating composite materials have the advantages of low density, excellent thermal conductivity, good acoustic conductivity, etc., and are widely used in thermal management, electrical conductors, electromagnetic shielding and other fields. Among them, interpenetrating metal-polymer composite materials with foam metal as the skeleton and polymer as the matrix have attracted widespread attention because they can combine the comprehensive advantages of metal and polymer. In recent years, interpenetrating metal-polymer-based interpenetrating composite materials have been developed for use in the field of friction and wear. Among interpenetrating metal-polymers, open-cell metal foams have been introduced into the design of lubricating materials due to their advantages such as light weight, high thermal conductivity and large specific surface area; as for polymer matrices, most studies use easily cured thermosetting resins as interpenetrating matrices. Due to the difficulty in controlling the preparation process, there are currently few studies on foam metal-polymer interpenetrating composite materials.

[0003] Polytetrafluoroethylene is widely used in various friction parts due to its excellent self-lubricating properties. However, polytetrafluoroethylene itself has low thermal conductivity, low mechanical strength and poor wear resistance. During the friction process, it often fails to lubricate due to a large amount of wear, frictional thermal deformation and load-bearing deformation. In previous studies, functional fillers of different dimensions are usually used to compositely modify polytetrafluoroethylene to improve its thermal conductivity, wear resistance and mechanical strength. However, the low content of functional fillers in this method is often not enough to form a continuous phase, and the reinforcing effect on polytetrafluoroethylene is limited by the scale of the interface, making it difficult to significantly improve the performance of polytetrafluoroethylene. In combination with the above reasons, we composite three-dimensional interconnected foam metal with polytetrafluoroethylene to construct a structurally interpenetrating composite material to comprehensively improve the comprehensive performance of the composite material for application in the field of solid lubrication. In the study of interpenetrating polytetrafluoroethylene-foam metal, since thermoplastic polytetrafluoroethylene needs to be sintered and formed under high temperature conditions, the mismatch between the intrinsic thermal expansion coefficients of metal and polymer will lead to the separation of the interface between the two during high-temperature sintering, causing the decline of material performance.

[0004] Based on this, the present invention provides a fluorosilane interface modified foam metal-polytetrafluoroethylene interpenetrating phase composite material and a preparation method thereof. On the basis of the foam metal-polytetrafluoroethylene interpenetrating phase composite system, a fluorosilane coupling agent is used to modify the foam metal skeleton to improve the bonding of the foam metal-polytetrafluoroethylene three-dimensional continuous interface. In addition, combined with the regulation of the structural parameters of the foam metal and the preparation process of the composite material, the thermal conductivity, mechanical strength and wear resistance of the foam metal-polytetrafluoroethylene interpenetrating phase composite material are further improved. The prepared foam metal-polytetrafluoroethylene interpenetrating phase composite material modified by fluorosilane has good interface bonding and has the characteristics of high mechanical strength, high thermal conductivity and high wear resistance. Summary of the invention

[0005] The purpose of the present invention is to provide a fluorosilane interface modified foam metal-polytetrafluoroethylene interpenetrating phase composite material and a preparation method thereof in view of the problem that the comprehensive performance of traditional composite modified polytetrafluoroethylene lubricating materials is not ideal. By introducing a three-dimensional continuous foam metal skeleton and regulating its structural parameters, the mechanical strength and thermal conductivity of the polytetrafluoroethylene composite material are greatly improved; by modifying and modifying the interpenetrating phase composite material with a fluorosilane coupling agent, the three-dimensional continuous interface bonding is improved, and the comprehensive performance of the composite material is further improved.

[0006] 1. Preparation of fluorosilane interface modified metal foam-polytetrafluoroethylene interpenetrating phase composites A method for preparing a fluorosilane interface modified foam metal-polytetrafluoroethylene interpenetrating phase composite material comprises the following steps: 1) Interface modification: first add the fluorosilane coupling agent to the ethanol aqueous solution, use acetic acid to adjust the pH value to 2-6, and obtain the fluorosilane hydrolyzate; then add the foamed metal to the fluorosilane hydrolyzate, keep it warm and stir at room temperature-110℃, and hydrolyze it for 12-24h; after the reaction, take out the foamed metal, wash it with anhydrous ethanol until it is neutral, and finally dry it at 50-80℃; 2) Impregnation of polytetrafluoroethylene substrate: Under a vacuum condition of -0.03~-0.10Mpa, immerse the foamed metal after the interface modification by fluorosilane in step 1) in polytetrafluoroethylene emulsion for 10~30min, take it out after the bubbles are eliminated, and dry it at 90~130℃ for 60~120min to remove the solvent; repeat the above immersion-drying steps several times; 3) Sintering: placing the interface-modified metal foam-polytetrafluoroethylene interpenetrating composite material obtained in step 2) in a polytetrafluoroethylene sintering furnace and sintering at 350-390° C. for 100-400 min.

[0007] In step 1), the fluorosilane coupling agent is one or more of trifluoropropyltrimethoxysilane, perfluorooctyltriethoxysilane, perfluorodecyltrimethoxysilane and perfluorodecyltriethoxysilane; the foam metal is one or more of foam nickel, foam copper and foam iron, with 10 to 100 openings per inch and a porosity of 70% to 98%. The content of the fluorosilane coupling agent is 10 to 60% of the mass fraction of the modified foam metal.

[0008] In step 2), the mass concentration of the polytetrafluoroethylene emulsion is 30% to 65%, and the particle size of the polytetrafluoroethylene in the emulsion is 80 to 500 nm.

[0009] 2. Structural characterization of fluorosilane interface modified metal foam-polytetrafluoroethylene interpenetrating composites The interface modification of fluorosilane and the interface bonding of the prepared metal foam-PTFE interpenetrating composite material were analyzed by contact angle measurement, scanning electron microscopy and X-ray spectroscopy. The results are shown in the attached figure. Figure 1-3 shown.

[0010] Figure 1 The morphology and energy spectrum of the foamed metal skeleton modified by the fluorosilane interface of the present invention are shown in the figure. As can be seen from the figure, after the fluorosilane interface modification, there is a layer of fluorosilane on the surface of the metal skeleton, which proves the successful modification of the fluorosilane on the surface of the metal skeleton.

[0011] Figure 2 The contact angle test of the foam metal skeleton before and after the fluorosilane interface modification of the present invention is shown in the figure. As can be seen from the figure, after the fluorosilane interface modification, the foam metal skeleton changes from hydrophilic to hydrophobic, which further illustrates the successful modification of the fluorosilane on the surface of the metal skeleton; on the other hand, the hydrophobic metal skeleton is easier to combine with the hydrophobic polytetrafluoroethylene, which improves the bonding degree of the three-dimensional continuous interface of the interpenetrating composite material.

[0012] Figure 3 This is a structural comparison between a fluorosilane interface-modified metal foam-polytetrafluoroethylene interpenetrating composite material and a non-interface-modified metal foam-polytetrafluoroethylene interpenetrating composite material. As can be seen from the figure, without interface modification, the linear expansion coefficients of metal and polymer differ by more than one order of magnitude, which causes the high-temperature sintering process of polytetrafluoroethylene to cause interface separation with a size of more than 60μm, blocking the effective transfer of stress and heat energy from hard, highly thermally conductive metal to polytetrafluoroethylene. After interface modification, the metal foam and polytetrafluoroethylene are tightly bonded, and the interface spacing is only a few microns, so that the normal load, shear stress and ambient heat can be effectively transferred from the metal foam to the polytetrafluoroethylene matrix with a three-dimensional continuous interface as a bridge, thereby greatly improving the thermal conductivity, strength and friction and wear properties of the composite material.

[0013] 3. Performance evaluation of fluorosilane interface modified metal foam-polytetrafluoroethylene interpenetrating composites 1. Tensile strength test The specimens were processed into standard sizes and subjected to mechanical property tests on a universal testing machine. The test standard was GB / T1040.2-2006 and the tensile rate was 1 mm / min.

[0014] 2. Thermal conductivity test The samples prepared in Examples 1 to 3 were machined into square pieces of 20 mm×20 mm×4 mm and tested on a thermal conductivity tester according to ISO 22007-2. The data are listed in Table 1.

[0015] 3. Friction and wear performance The samples prepared in Examples 1 to 3 were machined into rectangular sheets with a length of 40 mm, a width of 15 mm, and a thickness of 2 mm. The friction and wear properties were tested using a UMT friction and wear tester, and the test environment temperature was 23±5°C. The upper specimen was an Al2O3 ceramic flat pin with a diameter of 4.7 mm. It was reciprocated under a load of 50 N and a frequency of 5 Hz, with a single stroke of 5 mm and a total stroke of 200 m. The test data are listed in Table 1.

[0016] Table 1 Properties of foam metal-polytetrafluoroethylene interpenetrating phase composite materials prepared in Examples 1-3 As shown in Table 1, the thermal conductivity of the fluorosilane interface modified foam metal-polytetrafluoroethylene interpenetrating phase composite material prepared by the present invention is 2.8~16.0W / (m·K), the friction coefficient is 0.09~0.16, and the wear rate is (0.04~6.3)×10 -5 mm 3 / Nm. It can be seen that the interpenetrating metal foam-polytetrafluoroethylene composite material modified by fluorosilane interface has excellent thermal conductivity, mechanical properties and friction and wear properties. In Comparative Example 1, the metal foam was not modified by fluorosilane interface, resulting in a lack of strong bonding between polytetrafluoroethylene and the metal foam, which limits the effective transfer of stress and heat energy, causing the thermal conductivity to drop significantly to 0.7 W / (m·K), and the tensile strength to drop slightly to 20MPa. At the same time, the wear rate increased sharply to 8.1×10 -5 mm 3 / Nm.

[0017] Based on the above excellent properties, this material is expected to be used in moving and load-bearing parts in the fields of aerospace, marine engineering, automotive industry, etc., thereby achieving the comprehensive advantages of lightweight, high strength, and friction reduction and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1The morphology and energy spectrum of the foam metal skeleton modified by fluorosilane interface modification of the present invention.

[0019] Figure 2 This is the contact angle test of the foam metal skeleton before and after the fluorosilane interface modification of the present invention.

[0020] Figure 3 The structure comparison of the fluorosilane interface-modified foam metal-polytetrafluoroethylene interpenetrating phase composite material of the present invention and the non-interface-modified foam metal-polytetrafluoroethylene interpenetrating phase composite material is shown. DETAILED DESCRIPTION

[0021] The present invention is further explained below with reference to specific embodiments.

[0022] Example 1 Take 6 g of nickel foam (porosity 95%, 60 pores per inch) and 300 g of excess polytetrafluoroethylene emulsion (polytetrafluoroethylene particle size 90 nm, mass percentage 55%).

[0023] 1) Interface modification 50g of anhydrous ethanol, 5g of deionized water and 2.4g of trifluoropropyltrimethoxysilane are prepared into a fluorosilane hydrolyzate; the pH value is adjusted to 5.0 with acetic acid; the foamed metal is added to the fluorosilane hydrolyzate, and the hydrolysis reaction is carried out by mechanical stirring at room temperature for 12 hours; after the reaction, the foamed metal is taken out, washed with anhydrous ethanol until neutral, and finally dried at 50°C; 2) PTFE emulsion matrix impregnation Under vacuum degree -0.10MPa, the interface modified foam metal in 1) is immersed in polytetrafluoroethylene emulsion for 10min, and after the bubbles are eliminated, it is taken out and dried at 90°C for 50min to remove the solvent; the above immersion-drying steps are repeated twice; 3) Sintering of composite materials The interface-modified metal foam-polytetrafluoroethylene interpenetrating composite material obtained in step 2) was placed in a polytetrafluoroethylene-specific sintering furnace and sintered at a temperature of 370° C. for 180 min. The properties thereof are shown in Table 1.

[0024] Example 2 Take 10 g of nickel foam (porosity 85%, number of pores per inch 100) and 360 g of excess polytetrafluoroethylene emulsion (polytetrafluoroethylene particle size 100 nm, mass percentage 45%).

[0025] 1) Interface assembly 80g of anhydrous ethanol, 8g of deionized water and 3g of perfluorodecyltrimethoxysilane were prepared into a fluorosilane hydrolysis solution; the pH value was adjusted to 3.0 with acetic acid; the foamed metal was added to the fluorosilane hydrolysis solution, and the hydrolysis reaction was carried out at 110°C with stirring for 24 hours; after the reaction, the foamed metal was taken out, washed with anhydrous ethanol until neutral, and finally dried at 60°C; 2) PTFE emulsion matrix impregnation Under vacuum degree -0.06MPa, the interface-modified foam metal in 1) was immersed in polytetrafluoroethylene emulsion for 15min, taken out after the bubbles were eliminated, and dried at 100°C for 60min to remove the solvent; the above immersion-drying steps were repeated 4 times; 3) Sintering of composite materials The interface-modified metal foam-PTFE interpenetrating composite material obtained in step 2) was placed in a PTFE-specific sintering furnace and sintered at 380°C for 260 min. Its properties are shown in Table 1 and its structural characterization is shown in Figure 1-3 .

[0026] Example 3 Take 20 g of nickel foam (porosity 80%, 80 pores per inch) and 500 g of excess polytetrafluoroethylene emulsion (polytetrafluoroethylene particle size 180 nm, mass percentage 50%).

[0027] 1) Interface assembly 120g of anhydrous ethanol, 12g of deionized water and 4g of perfluorodecyltriethoxysilane are prepared into a fluorosilane hydrolysis solution; the pH value is adjusted to 2.0 with acetic acid; the foamed metal is added to the fluorosilane hydrolysis solution, and the hydrolysis reaction is carried out at 110°C with stirring for 24 hours; after the reaction, the foamed metal is taken out, washed with anhydrous ethanol until neutral, and finally dried at 80°C; 2) PTFE emulsion matrix impregnation Under vacuum degree -0.08MPa, the interface modified foam metal in 1) was immersed in polytetrafluoroethylene emulsion for 20min, and after the bubbles were eliminated, it was taken out and dried at 110°C for 80min to remove the solvent; the above immersion-drying steps were repeated 6 times; 3) Sintering of composite materials The interface-modified foam metal-PTFE interpenetrating composite material obtained in step 2) was placed in a PTFE-specific sintering furnace and sintered at 375°C for 360 min. Its properties are shown in Table 1 and its structural characterization is shown in Figure 1-3 .

[0028] Comparative Example 1 Take 6 g of nickel foam (porosity 95%, 60 pores per inch) and 300 g of excess polytetrafluoroethylene emulsion (polytetrafluoroethylene particle size 90 nm, mass percentage 55%).

[0029] 1) PTFE emulsion matrix impregnation Under vacuum conditions of -0.10 MPa, immerse the foam metal in polytetrafluoroethylene emulsion for 10 minutes, take it out after the bubbles are eliminated, and dry it at 90°C for 50 minutes to remove the solvent; repeat the above immersion-drying steps twice; 2) Sintering of composite materials The interface-modified metal foam-polytetrafluoroethylene interpenetrating composite material obtained in step 2) was placed in a polytetrafluoroethylene-specific sintering furnace and sintered at a temperature of 370°C for 180 minutes. The properties thereof are shown in Table 1.

Claims

1. A method for preparing a fluorosilane interface modified foam metal-polytetrafluoroethylene interpenetrating phase composite material, characterized in that: The following steps are involved: 1) Interface modification: first add the fluorosilane coupling agent to the ethanol aqueous solution, use acetic acid to adjust the pH value to 2-6, and obtain the fluorosilane hydrolyzate; then add the foamed metal to the fluorosilane hydrolyzate, keep it warm and stir at room temperature-110℃, and hydrolyze it for 12-24h; after the reaction, take out the foamed metal, wash it with anhydrous ethanol until it is neutral, and finally dry it at 50-80℃; 2) Impregnation of polytetrafluoroethylene substrate: Under a vacuum condition of -0.03~-0.10Mpa, immerse the foamed metal after the interface modification by fluorosilane in step 1) in polytetrafluoroethylene emulsion for 10~30min, take it out after the bubbles are eliminated, and dry it at 90~130℃ for 60~120min to remove the solvent; repeat the above immersion-drying steps several times; 3) Sintering: placing the interface-modified metal foam-polytetrafluoroethylene interpenetrating composite material obtained in step 2) in a polytetrafluoroethylene sintering furnace and sintering at 350-390° C. for 100-400 min.

2. A method for preparing a fluorosilane interface modified foam metal-polytetrafluoroethylene interpenetrating phase composite material as claimed in claim 1, characterized in that: In step 1), the fluorosilane coupling agent is one or more of trifluoropropyltrimethoxysilane, perfluorooctyltriethoxysilane, perfluorodecyltrimethoxysilane and perfluorodecyltriethoxysilane; the foam metal is one or more of foam nickel, foam copper and foam iron, with 10 to 100 pores per inch and a porosity of 70% to 98%.

3. A method for preparing a fluorosilane interface modified foam metal-polytetrafluoroethylene interpenetrating phase composite material as claimed in claim 1, characterized in that: In step 1), the content of the fluorosilane coupling agent is 10-60% of the mass fraction of the modified foam metal.

4. A method for preparing a fluorosilane interface modified foam metal-polytetrafluoroethylene interpenetrating phase composite material as claimed in claim 1, characterized in that: In step 2), the mass concentration of the polytetrafluoroethylene emulsion is 30% to 65%, and the particle size of the polytetrafluoroethylene in the emulsion is 80 to 500 nm.

5. A fluorosilane interface modified metal foam-polytetrafluoroethylene interpenetrating phase composite material prepared by the method of claim 1.

Citation Information

Patent Citations

  • Porous foam metal based embedded type solid self-lubricating composite material and preparation method thereof

    CN101906549A

  • Preparation method for graphene damping composite material

    CN108117719A

  • Modified polytetrafluoroethylene composite material and preparation method thereof

    CN113024976A

  • KR20200036492A